Involuntary and voluntary autobiographical memory specificity as a function of depression. - Watson, L; Berntsen, D; Kuyken, W; Watkins, E (2013)
BACKGROUND AND OBJECTIVES: This study tests the hypothesis derived from the CaR-FA-X model (Capture and Rumination, Functional Avoidance and Executive Function model, Williams et al., 2007), that depressed individuals will be less specific during voluntary than involuntary autobiographical memory retrieval and looks at the relative contributions of rumination, avoidance and executive function to memory specificity. METHODS: Twenty depressed and twenty never depressed individuals completed a memory diary, recording 10 involuntary and 10 voluntary autobiographical memories. Psychiatric status (assessed with the Structured Clinical Interview for DSM-IV, SCID-1), psychopathology, rumination, avoidance and executive function were assessed prior to completion of the memory diary. RESULTS: Both groups were more specific during involuntary than voluntary memory retrieval. No overall group differences were identified. However, when non-remitted depressed participants were compared to partially remitted and never depressed participants the expected interaction was identified; non-remitted depressed individuals were less specific during voluntary, but not during involuntary recall. Consistent with theory, negative correlations between memory specificity, rumination and avoidance were also present. LIMITATIONS: The study presents an important yet preliminary finding which warrants further replication with a larger sample size. CONCLUSIONS: The findings provide support for a number of models of autobiographical memory retrieval in particular the CaR-FA-X model of memory specificity.